Numerical Study on Resistance of Stepped Planing Hull - Rayhan, Fajri Ashfi; Masrul, Andika; Khairullah Akbar, Arya; Anugerah Putra, Bima (Universitas Negeri Malang, 2023)
A stepped planing hull, also known as a step hull, is a hull modification that reduces the wetted surface area. Although this type of hull has proven effective in several ships, it is still rarely used. The step hull possesses numerous advantages that make it ideal for activities involving small and fast boats. However, regrettably, its full potential remains untapped at present. The purpose of this study was to identify the effect of variations in the angle of the step hull on resistance or drag. The study utilized the CFD method, and three hull configuration models were used at each change in hull step angle of 180º, 210º, 240º, and 270º. Configurations 1 and 2 have similarities in terms of rear hull length (600 mm), hull height (20 mm for configuration 1 and 30 mm for configuration 2), and deadrise angle (15° for configuration 1 and 20° for configuration 2). Configuration 3 has similarities with an 800 mm rear hull, 20 mm hull height, and 15° deadrise angle. It was found that as the Froude number increases, the coefficient of total resistance decreases. Conversely, as the Froude number increases, the resulting resistance also increases. The configuration with the highest resistance value corresponds to the alteration from configuration 2 with a hull step of 180°, and that the alteration from configuration 2 with a hull step of 270° corresponds to the configuration with the lowest resistance value. This study concludes that deadrise angle and the height of the step hull are the main factors that require careful consideration when designing ships that use a step hull. Therefore, this research provides an understanding of the step hull and can serve as a basis for the development of the step hull.